Collaboration and the semantic web social networks, knowledge networks, and knowledge resources - Brüggemann, Stefan; D’Amato, Claudia (Information Science Reference, 2012)
"This book showcases cutting-edge research on the intersections of Semantic Web, collaborative work, and social media research, exploring how the resources of so-called social networking applications, which bring people together to interact and encourage sharing of personal information and ideas, can be tapped by Semantic Web techniques" - Provided by publisher
Literaturverzeichnis Seite 322-355
Literaturangaben
Keywords: Social Media; Semantic Web; Aufsatzsammlung